2018
DOI: 10.1002/joc.5912
|View full text |Cite
|
Sign up to set email alerts
|

Marine climate variability based on weather patterns for a complicated island setting: The New Zealand case

Abstract: Understanding marine climate variability is important for coastal planning and marine operations. It is also particularly challenging for complicated settings (e.g., islands) and data‐poor regions. The aim of this work is to establish a relationship between daily synoptic atmospheric patterns, and wave and storm surge conditions around New Zealand waters, based on instrumental and reanalysis data. The daily predictor we developed is able to represent sea and swell wave conditions as well as storm surge variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Finally, even though the hindcast database covers a period from 1871 to 2010, when analysing the reconstructed series (not shown), we observed a sharp change in the storm surge behaviour in the middle of the 20th century due to inhomogeneities that are present in the atmospheric reanalysis (Krueger et al ., ; Rueda et al ., ). Most likely, the inhomogeneities are caused by the limited number of observations assimilated into 20CR (Krueger et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, even though the hindcast database covers a period from 1871 to 2010, when analysing the reconstructed series (not shown), we observed a sharp change in the storm surge behaviour in the middle of the 20th century due to inhomogeneities that are present in the atmospheric reanalysis (Krueger et al ., ; Rueda et al ., ). Most likely, the inhomogeneities are caused by the limited number of observations assimilated into 20CR (Krueger et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…For this purpose we used high-resolution SLP fields from 1979 to 2011, with a spatial resolution of 0.5 and hourly temporal resolution, from the global climate forecast system reanalysis (CFSR; Saha et al, 2010Saha et al, , 2014. These SLP fields have been shown to be adequate when defining representative synoptic patterns for GCMs classification (Perez et al, 2015) and have been successfully applied for weather types (WTs) classification in the New Zealand area (Rueda et al, 2019).…”
Section: Atmospheric Datamentioning
confidence: 99%
“…S2). Rueda et al (2019) used a method of weather typing to develop statistical predictors for storm surge and wave height in NZ based on statistical relationship with MSL pressure fields. The Kidson (2000) weather regimes are easily associated with the extreme storm-tide and skew-surge spatial clusters identified.…”
Section: Methodsmentioning
confidence: 99%
“…Kidson (2000) defined three weather 'regimes', characterized by: (i) frequent low-pressure troughs crossing the country, (ii) high-pressure systems to the north with strong zonal flow to the south of the NZ, and (iii) blocking patterns with high-pressure 125 systems more prominent in the south ( Figure S1). Rueda et al (2019) used a method of weather typing to develop statistical predictors for storm surge and wave height in NZ based on statistical relationship with MSL pressure fields. The Kidson (2000) weather regimes are easily associated with the extreme sea-level and skew-surge spatial clusters identified.…”
Section: Methodsmentioning
confidence: 99%
“…Numerical models, properly calibrated, provide a means of extending the extreme sea-level analyses to develop probabilistic assessments of total water level along the entire coastline. These can include combinations of tidal (e.g., Walters et al 2001), storm-surge and wave models (e.g., Gorman et al 2003;Rueda et al 2019), which can include both hindcasts and climate-change future-casts (Cagigal et al submitted). However, numerical storm-surge models for climate change typically do not include MSLA, which 340 is an important component of extreme sea level (for tidally-dominant coasts) and hence flooding exposure (e.g., Stephens et al 2014;Sweet & Park 2014), and which we have shown to be an important influence on the timing of extreme events.…”
Section: (2017)mentioning
confidence: 99%